'Pedagogies of cruelty' and the patriarchal order of the nation state: the falsos positivos as a paradigmatic example. - Giraldo, Isis (Postcolonial Studies, 2021)
This article explores an episode of mass atrocity that took place in Colombia in 2002-2010 under the rule of Álvaro Uribe: the falsos positivos, a subset of extrajudicial killings carried out by state armed forces in exchange for monetary bonuses, holidays and/or promotions whose victims were more than 3000 poor and mostly male people. Drawing from Rita Segato's work, I address this event from a perspective that re-centres patriarchy and coloniality. I argue that the very possibility of the killings' occurrence, staging, symbolic function and scale, and the nearly zero empathy they generated in the general population, was the result of a historical implementation of 'pedagogies of cruelty' that in the context of Colombia have successfully trained the urban classes into what I will denote 'selective desensitisation'. As an extreme enactment of the 'mandate of masculinity', these crimes constitute an event that entrenches the patriarchal order that underlies the modern-colonial nation state. Apart from providing an explanatory framework for an extraordinary example of lack of empathy for certain victims in the context of Colombia, I aim to expand Segato's concept of 'pedagogies of cruelty' so as to demonstrate its immense analytical potential in the current global political landscape.